Rescued by Europe? Social and Labour Market Reforms in Italy from Maastricht to Berlusconi - Ferrera, Maurizio (Changing Welfare States, 2004)
As a result of its political and economic turmoil for much of the postwar period, Italy was considered the "bad seed" in the European community. Harsh ideological divisions, chronic executive instability, inefficient bureaucracy, uneven socio-economic development, organized crime and unbalanced public finances all contributed to this negative perception. Yet a massive economic and social overhaul was launched in the 1990s as part of Italy's efforts to meet the famous Maastricht requirements in order to join the Economic and Monetary Union (EMU). This book examines those processes and skillfully analyzes their consequences by exploring the effect they had on governmental and social actions. "Two of Italy's foremost public policy specialists, Ferrera and Gualmini are well placed to tell the story of how Italian political élites, long oriented towards buying off opposition and vested interests by expanding a bloated public debt,were finally confronted with reality by EMU membership criteria. Rescued by Europe is both a fascinating narrative of how governments, employers and unions responded to the EMU imperatives, and an in-depth analysis of how Italy's idiosyncratic labour markets and welfare system function, both for good and ill." Martin Rhodes Professor of European Public Policy, European University Institute, Florence, Italy Maurizio Ferrera is professor of social policy at the University of Pavia, Italy, and a member of the Italian National Commission on Social Exclusion. Elisabetta Gualmini is professor of administrative science at the University of Bologna, Italy.